Abundance and Diurnal Trends of Fluorescent Bioaerosols in the Troposphere over Mt. Tai, China, in Spring. Issue 7 (1st April 2019) - Yue, Siyao; Ren, Lujie; Song, Tianli; Li, Linjie; Xie, Qiaorong; Li, Weijun; Kang, Mingjie; Zhao, Wanyu; Wei, Lianfang; Ren, Hong; Sun, Yele; Wang, Zifa; et al.
Abstract: Primary biological aerosol particles are ubiquitous in the global atmosphere and can affect cloud formation, deteriorate air quality, and cause human infections. Mt. Tai (1, 534 m a.s.l.) is an elevated site in the North China Plain where atmospheric aerosols reflect both regional advection and long‐range transport. In this study, we deployed a Wideband Integrated Bioaerosol Sensor (WIBS‐4A) and collected total suspended particles and eight‐stage size‐segregated aerosol samples at the summit of Mt. Tai in spring from 21 March to 8 April 2017 to quantify the abundance, size distributions, and diurnal variations of fluorescent bioaerosols and to investigate the effect of different fluorescence thresholds of WIBS for ambient bioaerosol recognition. During the whole sampling period, the number concentration of fluorescent particles (>0.8 μm) was 647 ± 533 L −1, accounting for 26.9% ± 10.0% by number of the total particles in that size range. Three‐dimensional excitation‐emission matrix fluorescence of water‐soluble organic matter in size‐segregated aerosols shows that humic‐like substances (HULIS) are mainly in the fine mode (<2.1 μm) while protein‐like substances are mainly in the coarse mode (>2.1 μm). From the diurnal variation, it is shown that bioaerosols can undergo transformation during long‐range transport and contribute to HULIS. For bioaerosol recognition, we find that 6σ‐threshold can lead to better classification of fluorescent aerosol particles for fungal spores. Overall, our results constrain the abundance of primary bioaerosols in the troposphere over East Asia and elucidate the processes for their evolution via mountain/valley breezes and long‐range transport. Key Points: Fluorescent particles (>0.8 μm) account for 26.9% on average by number of the total particles in that size range over Mt. Tai in spring Bioaerosols are shown to undergo transformation during long‐range transport and contribute to HULIS For bioaerosol recognition, 6σ‐threshold can lead to better classification of fungal spores